Duszpasterstwo i życie religijne parafii Rembieszyce w latach 1800–1945. Z dziejów społeczności lokalnej - Karkocha, Małgorzata (Przegląd Nauk Historycznych, 2013)
The Rembieszyce Parish is located in the province of Kielce, in the commune of Małogoszcz and has been composed by four settlements: Rembieszyce, Karsznice, Mieronice and Wola Tesserowa. It was founded in 1438 with the efforts of Odrowąż family. It is dedicated to the Holy Apostles Peter and Paul. Presented article aims to show the religious life of the Rembieszyce Parish in the years 1800–1945. The Author’s researches efforts were focused on the external aspects of religious life, especially on religious practices. In this article Author also discussed the church teaching and the activities of the social and religious organizations. The basic sources for the Author researches are collected in the Archives of the Diocese of Kielce, and – to a lesser extent – in the Archive of the Parish Rembieszyce. Among them are: consistorial files, reports of the dean and pastoral visitation, school records and population statistics. The Author also used the parish registers of births, marriages and deaths, stored in several archives (Archives of the Kielce Diocese, State Archive in Kielce, Archive of the Rembieszyce Parish). This article is also complemented by other materials, such as correspondence or newspapers.